Can the FUT2 Non-secretor Phenotype Associated With Gut Microbiota Increase the Children Susceptibility for Type 1 Diabetes? A Mini Review - Giampaoli, Ottavia; Conta, Giorgia; Calvani, Riccardo; Miccheli, Alfredo (Frontiers in Nutrition, 2020)
The global toll of type 1 diabetes (T1D) has steadily increased over the last decades. It is now widely acknowledged that T1D pathophysiology is more complex than expected. Indeed, a multifaceted interplay between genetic, metabolic, inflammatory and environmental factors exists that leads to heterogeneous clinical manifestations across individuals. Children with non-secretor phenotype and those affected by T1D share low abundance of Bifidobacteria, low content of short-chain fatty acids, intestinal phosphatase alkaline and a high incidence of inflammatory bowel diseases. In this context, host-gut microbiota dyad may represent a relevant contributor to T1D development and progression due to its crucial role in shaping host immunity and susceptibility to autoimmune conditions. The FUT2 gene is responsible for the composition and functional properties of glycans in mucosal tissues and bodily secretions, including human milk. FUT2 polymorphisms may profoundly influence gut microbiota composition and host susceptibility to viral infections and chronic inflammatory disease. In this minireview, the possible interplay between mothers’ phenotype, host FUT2 genetic background and gut microbiota composition will be discussed in perspective of the T1D onset. The study of FUT2-gut microbiota interaction may add a new piece on the puzzling T1D etiology and unveil novel targets of intervention to contrast T1D development and progression. Dietary interventions, including the intake of α-(1-2)-fucosyl oligosaccharides in formula milk and the use of specific prebiotics and probiotics, could be hypothesized.